2005
DOI: 10.1111/j.1365-294x.2005.02769.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population structure of Cynopterus fruit bats in peninsular Malaysia and southern Thailand

Abstract: The extent to which response to environmental change is mediated by species-specific ecology is an important aspect of the population histories of tropical taxa. During the Pleistocene glacial cycles and associated sea level fluctuations, the Sunda region in Southeast Asia experienced concurrent changes in landmass area and the ratio of forest to open habitat, providing an ideal setting to test the expectation that habitat associations played an important role in determining species' response to the opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 100 publications
(133 reference statements)
2
48
0
Order By: Relevance
“…Clinal variation in terms of size of this species was discussed by Storz et al (2001) and our observations (unpublished data) indicate that C. sphinx is not highly adaptable in Peninsular Malaysia incongruent with observations of Bates et al (2008b). Although widespread the abundance of this species is determined by the type of vegetation sampled (Campbell et al 2006). In Gunung Stong State Park the forearm length of this species was 74.52卤3.87 mm and this species was netted in the hill vegetation and near bamboo plots beside the forest fringe.…”
Section: Balionycteris Maculatamentioning
confidence: 97%
See 1 more Smart Citation
“…Clinal variation in terms of size of this species was discussed by Storz et al (2001) and our observations (unpublished data) indicate that C. sphinx is not highly adaptable in Peninsular Malaysia incongruent with observations of Bates et al (2008b). Although widespread the abundance of this species is determined by the type of vegetation sampled (Campbell et al 2006). In Gunung Stong State Park the forearm length of this species was 74.52卤3.87 mm and this species was netted in the hill vegetation and near bamboo plots beside the forest fringe.…”
Section: Balionycteris Maculatamentioning
confidence: 97%
“…brachyotis Forest has been identified (Abdullah 2003;Campbell et al 2004Campbell et al , 2006Campbell et al , 2007Jayaraj 2009;Fong 2011;Jayaraj et al 2012). We took the liberty of separating the new form C. cf.…”
Section: Balionycteris Maculatamentioning
confidence: 99%
“…These species have reduced genetic diversity in the south of Thailand relative to the north with evidence of recent expansion indicating that the peninsular region was recently re-colonised from the north, and that prior to this forest habitat was scarce or absent. However, another study of forest and non-forest dependent bats found inconclusive relationships between ecotype and population history (Campbell et al, 2006). In the case of An.…”
Section: Pleistocene Climatic Effectsmentioning
confidence: 99%
“…When repeated several times throughout the Pleistocene, this system has the potential to generate a lot of diversity. This hypothesis has been supported by low levels of genetic divergence between populations of some Sunda shelf mammals (Campbell et al, 2004(Campbell et al, , 2006Gorog et al, 2004;Lucchini et al, 2005;Roos et al, 2003). However, the vegetation during the Pleistocene glacial periods was undoubtedly very different from the present, and the interactions between climate and sea level and their effects on the distribution of the fauna and flora is complex (van den Bergh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%